Bioactivities of phenolic blend extracts from Chilean honey and bee pollen. Issue 1 (1st January 2019) - Velásquez, P.; Montenegro, G.; Giordano, A.; Retamal, M.; Valenzuela, L. M.
ABSTRACT: It is known that polyphenolic extracts have antibacterial activity, but usually with not very broad spectrum of action. To enhance its individual antibacterial effect, to combine different extracts has been proposed. In this work, the combined antibacterial effect of 3 extracts and their mixtures (Ulmo and Quillay honeys, multifloral pollen) was evaluated. Their polyphenol content was quantified by HPLC-DAD analysis. E. coli, S. aureus, Salmonella spp, Pseudomonas spp, L. acidophilus, and B. thermosphacta were used as foodborne pathogenic-spoilage strains in the antibacterial assays. Polyphenol-target bacteria relationships were established. Results showed that all extracts and their combinations have activity against all strains. Relationships were established between all pathogenic strains with 4 phenolic acids and 2 flavonoids, and 2 spoilage strains with 3 phenolic acids and 3 flavonoids. These findings will contribute to the rapid assessment of mixtures of outstandingly antibacterial extracts to be applied in the food industry.